JURIDICIAL ANALYSIS OF TRANSFER PRICING DOCUMENTS IN RESPECT OF TAX AVOIDANCE FOR MULTINATIONAL COMPANIES - Angelina Clarabella; Edi Pranoto (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2021)
Essential principle within business world definitely would be maximizing profit and minimizing capital. Hence many companies would struggleand develop their own ways to avoid taxes as much as they could. Tax avoidance which is taken illegally would disrupt government's revenue indeed. This paper discusses normative juridical approach to examine problems as 1. How does transfer pricing documents could help to diagnose tax avoidance practice within companies? 2. How to prevent the occurrence of transfer pricing's shortcomings? This would highlight the transfer pricing's existence to eliminate illegal practice of tax avoidancewithin multinational companies and some methods to prevent the shortcomings of transfer pricing. The results shows that 1. transfer Pricing documents are useful for diagnosing tax avoidance practices in multinational companies through an analysis of fairness and business practice and 2. in order to prevent deficiencies in Transfer Pricing documents, the Government must establish a cooperative relationshipbetween companies and reliable tax administrations. such as through AEoI (Automatic Exchange of Information) between countries to encourage transfer pricing inspection processes in multinational companies. The government should conduct cooperative relationship between the companies and tax administration to encourage the process of transfer pricing examination within multinational companies in precise scheduled time frame. Fair and favorable assessment of business report is significant due to undermine unnecessary cost and improper result.The competence and professional judgement from the Directorate General of Taxes are substantial.